THE ROLE OF TEACHERS IN ISLAMIC EDUCATION: FOUNDATIONS, DUTIES AND CHALLENGES - Pajala, Kiflin (Bajang Institute, 2024)
This article discusses the important role of teachers in Islamic education, outlining the foundations, tasks and challenges faced in this context. The research method used in this article is using a qualitative method using the form of library research to obtain data. This research uses library data sources in the form of books, journals and other sources collected from several references related to the title of this article. The technique used in collecting data is by looking for reference sources related to the discussion of this article, then analyzing the content of the data that has been collected. The results of this research show that the foundation of the teacher's role in Islamic education includes a deep understanding of religious teachings, the ability to transfer Islamic values, and acting as a moral role model for students. The teacher's main task is to develop students' potential holistically, including spiritual, intellectual and emotional aspects, as well as instilling noble morals in accordance with Islamic principles. The challenges faced by teachers in Islamic education include limited resources, rapid technological developments, and complex social and cultural dynamics. Through a comprehensive and adaptive approach, teachers are expected to be able to overcome these various obstacles and continue to carry out their role effectively in forming a generation with morals and broad knowledge within the Islamic framework.